Penerapan Diabetes Self Management Education bagi Lansia yang Mengalami Diabetes Mellitus - Afina Muharani Syaftriani; Maria Haryanti Butar-butar; Sri Lasmawanti; Yuniati Yuniati; Maya Ardilla Siregar (Lembaga Pengembangan Kinerja Dosen, 2021)
Diabetes Mellitus (DM) is a complex disease that affects especially the elderly. Efforts to control DM are the aim of controlling the impact of complications. One management that can be carried out by nurses as health workers is to provide continuous health education (education). One educational program that can be carried out is Diabetes Self Management Education (DSME). The aim of implementing this community service is to provide education to the elderly regarding the implementation of Diabetes Self Management Education (DSME). The method used in implementing this community service is by providing counseling through lectures and giving leaflets containing outreach material in Hamlet 1B Wampu, Pantai Gemi Village, Stabat District, Langkat Regency, North Sumatra. The targets for implementing the activity are elderly people with DM in Hamlet 1B Wampu, Pantai Gemi Village, Stabat District, Langkat Regency, North Sumatra. The results of this community service have had a positive impact on the parties involved, especially for the elderly with DM in Hamlet 1B Wampu, Pantai Gemi Village. Elderly people with DM can increase their knowledge, skills and improve their ability to carry out optimal self-care. Apart from that, elderly people with DM can also improve their self-management in managing DM more effectively by checking blood sugar regularly, eating a healthy diet, doing physical activity, taking medication according to the doctor's prescription, and dealing with stress caused by DM.